2013
DOI: 10.1155/2013/320415
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Nonlinear Fractional Differential Equations of Arbitrary Order with Riemann-Liouville Type Multistrip Boundary Conditions

Abstract: We develop the existence theory for nonlinear fractional differential equations of arbitrary order with Riemann-Liouville type boundary conditions involving nonintersecting finite many strips of arbitrary length. Our results are based on some standard tools of fixed point theory. For the illustration of the results, some examples are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The nonlocal boundary conditions are found to be of great utility in modeling the changes happening within the domain of the given scientific phenomena, while the concept of integral boundary conditions is applied to model the physical problems, such as blood flow problems on arbitrary structures and ill-posed backward problems. For some recent works on fractional order differential equations involving Riemann-Liouville, Caputo, and Hadamard type fractional derivatives, equipped with classical, nonlocal, and integral boundary conditions, we refer the reader to a series of papers [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlocal boundary conditions are found to be of great utility in modeling the changes happening within the domain of the given scientific phenomena, while the concept of integral boundary conditions is applied to model the physical problems, such as blood flow problems on arbitrary structures and ill-posed backward problems. For some recent works on fractional order differential equations involving Riemann-Liouville, Caputo, and Hadamard type fractional derivatives, equipped with classical, nonlocal, and integral boundary conditions, we refer the reader to a series of papers [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…η m < 1 and γ i ∈ R are appropriately chosen constants. The strip boundary condition in problem (1) can be regarded as a Riemann-Liouville type fractional integral boundary conditions involving non-intersecting finite many strips of arbitrary length, for example, see [5,7,20]. The paper is organized as follows: In Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Fractional calculus has also emerged as a powerful modeling tool for many real world problems. For examples and recent development of the topic, see ( [1,2,3,4,5,6,7,14,16,17,18,19,20]). However, it has been observed that most of the work on the topic involves either Riemann-Liouville or Caputo type fractional derivatve.…”
Section: Introductionmentioning
confidence: 99%